Construction and isolation of a transforming murine retrovirus containing the src gene of Rous sarcoma virus. - Anderson, S M (1983)
Recombinant murine retroviruses containing the src gene of the avian retrovirus Rous sarcoma virus were isolated. Such viruses were isolated from cells after transfection with DNAs in which the src gene was inserted into the genome of the amphotropic murine retrovirus 4070A. The isolated viruses had functional gag and pol genes, but they were all env defective since the src gene was inserted in the middle of the env gene coding region. Infectious transforming virus could be isolated only from cells transfected with DNA constructions in which the src gene was in the same polarity as that of a long terminal repeat of the amphotropic viral genome. These recombinant viruses encoded a pp60src protein with a molecular weight similar to that of the Schmidt-Ruppin strain of Rous sarcoma virus. In addition, the src protein(s) of these recombinant viruses was as active as protein kinases in the immune complex protein kinase assay. Intravenous injection of helper-independent Moloney and Friend murine leukemia virus pseudotypes of the src recombinant viruses into 6-week-old NIH Swiss mice resulted in the appearance of splenic foci within 2 weeks, splenomegaly and, later after infection (8 to 10 weeks), anemia. Infectious transforming virus could be recovered from the spleens of diseased animals. Such viruses encoded pp60src but not p21ras or mink cell focus-forming virus-related glycoproteins.